Advanced pancreatic cancer with KRAS wild-type and EGFR-sensitive mutation respond favorably to furmonertinib: A case report - Ma, Xiaoting; Liu, Xiu; Ou, Kai; Zhang, Manman; Gao, Lizhen; Yang, Lin (Frontiers in Oncology, 2023)
Pancreatic cancer is a leading cause of cancer deaths; treatment options are limited and mostly ineffective. The patient we report had an EGFR exon 19 deletion and disease progression in the short term after receiving three front-line treatment regimens. We administered furmonertinib and observed tumor shrinkage and a decreased CA19-9 level. The progression-free survival following treatment with furmonertinib was 4.7 months and no adverse effects were observed; however, the patient did not benefit from subsequent nimotuzumab-based therapy. Targeted therapy driven by the detection of genetic signatures in this patient with refractory advanced pancreatic cancer had a potential clinical benefit.